Morphological Properties Of Zinc Oxide Nanostructures Prepared By Electrochemical Process - Mah, Chai Fong (2018)
In this work, two electrochemical methods, i.e. electrochemical deposition and anodization have been used to grow ZnO nanostructures. Cube- like nanostructures has been synthesized by electrochemical deposition, in which a mixture of equimolar zinc chloride (ZnCl2) and potassium chloride (KCl) with different concentration has been served as electrolyte. The effect of electrolyte concentration against the physical structural changes on the nanostructure was observed. The average size of the deposited nanomaterial was decreased from 207 nm to 102 nm with increase of electrolyte concentration. X-ray diffraction (XRD) pattern revealed the as-deposited nanostructures were converted from amorphous to hexagonal wurtzite ZnO phase after heat treatment at 600 °C for 3 hours.